Development and reliability of a Turkish version of the Short Form-Joint Protection Behavior Assessment (JPBA-S) - TONGA, EDA (HANLEY & BELFUS-ELSEVIER INC, 2016)
Study design: Clinical measurement. Purpose: To adapt the original JPBA-S to a Turkish version (TUR-JPBA-S) and to investigate its reliability in assessing patients with rheumatoid arthritis (RA). Methods: Twenty-two participants with RA and 21 healthy people were videotaped while performing tasks listed in the TUR-JPBA-S. Two raters scored the video recordings for to evaluate inter-rater reliability. One rater re-analyzed the recordings at a different time point for intra-rater reliability. Participants with RA were asked to perform the same tasks after three to four weeks which was also recorded to evaluate test-retest reliability. Results: Internal consistency (Cronbach's alpha value) was found to be high (0.89) for participants with RA. Our results demonstrate excellent intra-rater (ICC: 0.99, SEM 1.2) inter-rater (ICC: 0.99, SEM 1.7) reliability, apart from excellent test-retest reliability (ICC: 0.96). Conclusion: The TUR-JPBA-S is a valid and reliable instrument for assessing JP behavior in patients with RA in Turkey. (C) 2016 Hanley & Belfus, an imprint of Elsevier Inc. All rights reserved.
Keywords: Joint protection behavior assessment; Turkish version; Reliability; Rheumatoid arthritis; RANDOMIZED CONTROLLED-TRIAL; RHEUMATOID-ARTHRITIS; PEOPLE; OUTCOMES; PROGRAM; VALIDATION; EDUCATION; ADAPTATION; VALIDITY; HEALTH